SARS-CoV-2 shedding dynamics and transmission in immunosuppressed patients. Issue 1 (31st December 2022) - Lee, Jee-Soo; Yun, Ki Wook; Jeong, Hyeonju; Kim, Boram; Kim, Man Jin; Park, Jae Hyeon; Shin, Ho Seob; Oh, Hyeon Sae; Sung, Hobin; Song, Myung Gi; Cho, Sung Im; Kim, So Yeon; et al.
ABSTRACT: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern have been emerging. However, knowledge of temporal and spatial dynamics of SARS-CoV-2 is limited. This study characterized SARS-CoV-2 evolution in immunosuppressed patients with long-term SARS-CoV-2 shedding for 73–250 days, without specific treatment. We conducted whole-genome sequencing of 27 serial samples, including 26 serial samples collected from various anatomic sites of two patients and the first positive sample from patient 2's mother. We analysed the intrahost temporal dynamics and genomic diversity of the viral population within different sample types. Intrahost variants emerging during infection showed diversity between individual hosts. Remarkably, N501Y, P681R, and E484K, key substitutions within spike protein, emerged in vivo during infection and became the dominant population. P681R, which had not yet been detected in the publicly available genome in Korea, appeared within patient 1 during infection. Mutually exclusive substitutions at residues R346 (R346S and R346I) and E484 (E484K and E484A) of spike protein and continuous turnover of these substitutions occurred. Unique genetic changes were observed in urine samples. A household transmission from patient 2 to his mother, at least 38 days after the diagnosis, was characterized. Viruses may differently mutate and adjust to the host selective pressure, which could enable the virus to replicate efficiently for fitness in each host. Intrahost variants could be candidate variants likely to spread to the population eventually. Our findings may provide new insights into the dynamics of SARS-CoV-2 in response to interactions between the virus and host.